Moment of truth: why Aha! Experiences are correct - Danek, Amory H.; Salvi, Carola (The journal of creative behavior, 2020)
Having a sudden insight is often associated with inherent confidence, enough for Archimedes to run naked through the streets shouting “Eureka!”. Recent evidence demonstrates that public displays of enthusiasm, such as the ancient polymath's, are actually supported by a higher likelihood of being correct.